Biomimetic Compartments Scaffolded by Nucleic Acid Nanostructures. Issue 26 (18th March 2019) - Fu, Jinglin; Oh, Sung Won; Monckton, Kristin; Arbuckle‐Keil, Georgia; Ke, Yonggang; Zhang, Ting
Abstract: The behaviors of living cells are governed by a series of regulated and confined biochemical reactions. The design and successful construction of synthetic cellular reactors can be useful in a broad range of applications that will bring significant scientific and economic impact. Over the past few decades, DNA self‐assembly has enabled the design and fabrication of sophisticated 1D, 2D, and 3D nanostructures, and is applied to organizing a variety of biomolecular components into prescribed 2D and 3D patterns. In this Concept, the recent and exciting progress in DNA‐scaffolded compartmentalizations and their applications in enzyme encapsulation, lipid membrane assembly, artificial transmembrane nanopores, and smart drug delivery are in focus. Taking advantage of these features promises to deliver breakthroughs toward the attainment of new synthetic and biomimetic reactors. Abstract : DNA‐scaffolded compartments provide the ability to engineer various nano‐objects with controlled geometry and spatial confinements, which are utilized to construct biomimetic components of liposome confinement, artificial transmembrane nanopores, biochemical pathway encapsulation, and smart nanorobots. Taking advantage of these features promises to deliver breakthroughs toward the building of a synthetic cell.